Polyene Macrolactams from Marine Micromonospora sp. - Zhao, Wei; Zhou, Jian; Sun, Fei; Jiang, Honglei; Lin, Ru; Zhou, Jingming; Chen, Xiuming; Butt, Usman-Dawood; Wang, Yi-Nuo; Jiang, Hong; Wu, Bin (Natural Products Journal, The, 2026)
IntroductionThree novel macrolactams, FW8-1 (1), FW8-4 (2), and FW60-20 (3), were isolated from a culture of Micromonospora sp. The structures of these compounds were elucidated using Mass Spectrometry (MS) and comprehensive Nuclear Magnetic Resonance (NMR) analyses.MethodsThe relative configurations of compounds 1-3 were assigned through theoretical calculations of their NMR spectra.ResultsThe isolation and determination of the relative configurations of these macrolactams have provided fresh perspectives on the biosynthetic pathways, leading to the formation of polyene macrolactams.ConclusionFurther, virtual screening and bioactivity predictions have suggested compounds 1-3 to possess potential anti-tumor, anti-inflammatory, and neuroprotective properties.
Keywords: theoretical calculations